Interpreting 2D Materials Bio‐Nano Interactions: Influence of Aggregation Status, Protein Corona, Cell Culture Media, and Cell Types. Issue 17 (12th August 2021) - Mei, Kuo‐Ching; Costa, Pedro M.; Kreuzer, Martin; Al‐Jamal, Khuloud T.
Abstract: Huge interests have been drawn to 2D nanomaterials for biomedical applications; however, the 2D bio‐nano interface is largely dependent on the biological environment. Hard protein corona (HC)‐dependent bio‐nano interactions are highly sensitive to material surface functional group changes. Alterations in HC change the colloidal stability of the nanomaterials hence changes the material presentation to cells, which ultimately affect bio‐nano interactions. Here graphene oxide (GO) is used as an exemplar 2D platform to investigate HC‐dependent and colloidal stability‐dependent bio‐nano interactions on contrasting non‐phagocytic A549 cells and phagocytic J774 cells, using lactate dehydrogenase (LDH) assay and principal components analysis (PCA) of cellular IR spectra obtained by label‐free synchrotron radiation‐based Fourier‐transform IR microspectroscopy (SR‐FTIR). Abstract : The interpretation of bio‐nano interactions for 2D nanomaterials requires extra care. Minor surface chemistry changes could lead to various serum protein binding levels (hard corona/HC) that result in variable colloidal stabilities and aggregation status in biological media. Nano‐toxicity or biocompatibility findings collectively depend on cell culture media formulation, cell types, material exposure time, and the 2D/2.5‐3D material presentation.